A Perspective on Training in Public Policy Evaluation through the Lens of Omnijetivity - López Rodríguez, Jenny Elisa (2026)
The purpose of this article is to present an overview of the achievements and challenges in postgraduate training within the field of public policy evaluation from the perspective of omnijetivity. It adopts this epistemological stance based on the understanding that social problems fail to move toward transformative solutions due to the explanatory and action frameworks used to address them; that is, their limitations are rooted in the epistemological and methodological perspectives that underpin them. The study involves the systematization of postgraduate teaching experiences in public policy evaluation during the 2014-2022 period at the Universidad Nacional de Colombia (UN), la Pontificia Universidad Javeriana (PUJ) and the Escuela Superior de Administración Pública (ESAP). The methodology focused on Participatory Action Research (PAR), participant observation, ethnography, and meta-evaluation strategies, all of which are consistent with the proposed approach. Among the most relevant results, the study highlights the importance of epistemological debate in postgraduate training as a principle of epistemic justice; the urgent need for methodological and pedagogical developments based on the logic of omnijetivity; and the necessity of establishing greater articulation between training and research processes.